Corpo-drone: governamentalidade algorítmica e a modulação espaço-imagética - Carmelini, Leandro (2021)
This text deals with space-imagery modulation by means of algorithms into four movements. The first presents augmented reality lenses as devices capable of reconnecting two technological lines: the imagery and the locomotive. The second discusses cross-cuttings between cybernetics and artificial intelligence, the unlimited scope of algorithmic action, and the renewal of longings for overtaking mankind. The third addresses the algorithms as cognitive traps. Finally, we seek clues in facial biometrics and autonomous car systems to discuss the incorporation of visual space digitization systems. From the sum of these topics, we propose the notion of body-drone.